2015
DOI: 10.1186/s12906-015-0687-3
|View full text |Cite
|
Sign up to set email alerts
|

Views and experiences of healthcare professionals towards the use of African traditional, complementary and alternative medicines among patients with HIV infection: the case of eThekwini health district, South Africa

Abstract: BackgroundMany patients with human immunodeficiency virus infection use traditional, complementary, and alternative medicines and other practices to combat the disease, with some also using prescribed antiretroviral therapy provided by the public health sector. This study aimed to establish the awareness of public sector biomedical health care providers on the use of traditional, complementary and alternative medicines by HIV-infected patients who also used highly active antiretroviral therapy, and to determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 23 publications
0
7
0
1
Order By: Relevance
“…Reported prevalence estimates of lifetime use of CAM among People Living with HIV and AIDS (PLWHA) reached up to 90% [9], with the most commonly reported forms of CAM used being vitamins and herbs, followed by prayer, meditation, and spiritual healing [7, 9, 10]. Such a high prevalence of CAM use among PLWHA could be due to a variety of reasons, such as the desire to strengthen immunity, improve general wellbeing, and be actively involved in the management of their disease [6, 1114]. Lessening side effects of Highly Active Anti-Retroviral Therapy (HAART) is another reason why PLWHA resort to CAM [6, 15].…”
Section: Introductionmentioning
confidence: 99%
“…Reported prevalence estimates of lifetime use of CAM among People Living with HIV and AIDS (PLWHA) reached up to 90% [9], with the most commonly reported forms of CAM used being vitamins and herbs, followed by prayer, meditation, and spiritual healing [7, 9, 10]. Such a high prevalence of CAM use among PLWHA could be due to a variety of reasons, such as the desire to strengthen immunity, improve general wellbeing, and be actively involved in the management of their disease [6, 1114]. Lessening side effects of Highly Active Anti-Retroviral Therapy (HAART) is another reason why PLWHA resort to CAM [6, 15].…”
Section: Introductionmentioning
confidence: 99%
“…Este é um objetivo atingível, em nome de uma boa prática clínica (2). O caso especial de pacientes polimedicados, como os pacientes com SIDA, mostra que o desconhecimento dos profissionais de saúde sobre a utilização de produtos à base de plantas por parte dos seus pacientes é elevado (48 em 94, segundo Nlooto), podendo este desconhecimento ser relevante na perceção de eventuais efeitos adversos que possam surgir com a concomitante utilização das terapêuticas (18)complementary, and alternative medicines and other practices to combat the disease, with some also using prescribed antiretroviral therapy provided by the public health sector. This study aimed to establish the awareness of public sector biomedical health care providers on the use of traditional, complementary and alternative medicines by HIV-infected patients who also used highly active antiretroviral therapy, and to determine whether this was based on patients seen or cases being reported to them.…”
Section: Methodsunclassified
“…Although there is a perception that herbal medicines are safe, in fact this is not always the case when used in concomitance with other prescription medicines (1,17) Thus, optimization of medical care in which physicians are aware of the potential risks and therapeutic benefits of indicating medicinal plants is an attainable goal in the name of good clinical practice (2). The special case of polymedicated patients, such as AIDS patients, shows that unawareness of health professionals about the use of herbal products by their patients (48 in 94, according to Nlooto) may be relevant in the perception and understanding of potential adverse effects that may arise with the concomitant use of therapeutics (18) complementary, and alternative medicines and other practices to combat the disease, with some also using prescribed antiretroviral therapy provided by the public health sector. This study aimed to establish the awareness of public sector biomedical health care providers on the use of traditional, complementary and alterna-bito do procedimento completo de autorização da colocação no mercado para medicamentos convencionais.…”
Section: Introductionmentioning
confidence: 99%
“…The traditional healing system has been claimed to be illogical, lacking in both scientific validity and suitable policies for its products and practices [32,33]. However, other research suggests how THPs can be beneficial in the context of HIV/AIDS [3437]. Indigenous belief systems drive significant levels of medical pluralism with the continued use of traditional healing alongside ART care, particularly in rural populations [38–40].…”
Section: Introductionmentioning
confidence: 99%
“…While some studies have indicated that THPs lack the biomedical skills and knowledge to diagnose and treat HIV [34,35,44], THPs who are trained in HIV/AIDS have been used to educate patients about the causes and consequences of HIV, and have provided physical and psychosocial community-based HIV care [19,45–47]. A quantitative study conducted among patients consulting THPs in the context of HIV/AIDS found that PLHIV did so owing to several complex health situations [28].…”
Section: Introductionmentioning
confidence: 99%